Molecular characterization and comparative genomics of multidrug resistant acinetobacter baumannii from Malaysia / Lean Soo Sum - Lean, Soo Sum (2016)
Hospital-acquired infections caused by multidrug resistant (MDR) Acinetobacter baumannii has become a serious problem due to the bacterium’s remarkable ability to develop resistance to all available antibiotics including carbapenems, the drug of choice for Acinetobacter infections. To better understand the biology and extent of drug resistance in locally isolated A. baumannii, 54 strains from sporadic cases of infection were collected from Hospital Sultanah Nur Zahirah (HSNZ) in Kuala Terengganu throughout 2011 and characterized. The 54 A. baumannii strains showed high resistance rates (>50%) to tetracycline, piperacillin-tazobactam, cefotaxime, ceftazidime, cefepime, levofloxacin, ampicillin-sulbactam, gentamicin, ciprofloxacin, tobramycin, doxycycline and amikacin with 39 strains (or 72.2%) classified as MDR. These MDR A. baumannii were then tested for susceptibility to polymyxin B, which is considered as the drug of last resort for the treatment of A. baumannii infections. Of concern, 14 of the MDR A. baumannii strains were polymyxin resistant and also categorized as extensive drug resistant (XDR). All 54 A. baumannii strains were subtyped by pulsed-field gel electrophoresis (PFGE). Dendrogram generated from the different ApaI pulsotypes showed that the strains were genetically diverse with carbapenem-resistant strains grouped into four main clusters whereas polymyxin-resistant strains were not clustered. To have a better understanding of the A. baumannii resistance mechanisms, one MDR (strain AC29) and two XDR strains (AC12 and AC30) were subjected to whole genome sequencing using the Illumina Genome Analyzer IIx. All three strains had genome sizes of ~3.8 Mbp and analysis of the loci used for multilocus sequence typing (MLST) showed that all three strains belonged to the ST195 lineage. All three strains harboured an approximately 23 kb AbaR4-type resistance island (RI) that interrupted the comM gene and contained the blaOXA-23 carbapenase gene within a Tn2006-like structure. This RI, designated AC12-RI1 in strain AC12, AC30-RI1 in strain AC30 and AC29-RI1 in strain AC29, also encode determinants for tetracycline and streptomycin resistance. A. baumannii AC12 harboured an RI that was not found in either AC29 or AC30: the 10.3 kb AC12RI-2 which contained determinants for aminoglycoside and β-lactam resistance. A smaller RI, the 7 kb Tn1548::armA which encoded determinants for aminoglycoside and macrolide resistance, was located in the chromosomes of AC12, AC29 and a 16 kb plasmid of AC30 designated pAC30b. Plasmid analysis showed that all three A. baumannii strains harboured an 8 kb cryptic plasmid. AC29 and AC30 harboured a similar ~70 kb conjugative plasmid while AC30 harboured the additional pAC30b. Genome analysis also revealed a multitude of efflux pumps and drug transporters in all three strains which could contribute to their multidrug-resistant phenotype. Mutations within lipopolysaccharide (LPS) biosynthesis (lpxA, lpxC, lpxD and lpsB) or modification genes (pmrCAB) were discovered in the polymyxin-resistant strains. Experimental evidence indicated that disruption in LPS biosynthesis and up-regulation of the LPS modification genes may have contributed to the development of polymyxin resistance. Comparative genome analysis of A. baumannii revealed the genetic basis of drug resistance in local clinical strains and the knowledge gained may help in containing the spread of MDR and XDR A. baumannii.